Finite Sample Power of Cliff-Ord-Type-Tests for Spatial Disturbance Correlation in Linear Regression - Krämer, Walter (Universitätsbibliothek Dortmund, 2002)
The paper considers tests against for autocorrelation among the disturbances in linear regression models that can be expressed as ratios of quadratic forms. It shows that such tests are in general not unbiased and that power can even drop to zero for certain regressors and spatial weight matrices. Whether or not this can happen is however easily diagnosed for given regressors and for given spatial weights.
Keywords: spatial autocorrelation; unbiased tests; power; 310